John G. Baker was right all along, Kalanchoe streptantha (Crassulaceae subfam. Cotyledonoideae) is a kitchingia: refining the circumscription of the Malagasy K. sect. Streptanthae, now a monotypic section in K. subg. Kitchingia - Smith, Gideon F. (Phytotaxa, 2025)
The circumscription of Kalanchoe sect. Streptanthae (Crassulaceae subfam. Cotyledonoideae), previously a two-species section, is amended to include only K. streptantha, so yielding it monotypic. The section is now included in K. subg. Kitchingia, no longer in K. subg. Bryophyllum, in which K. bogneri removed from it, is retained.